Use the Commutative Property to determine the missing step in proving the equivalence of 12a+10+a=10+a+12a.

Step 1: [missing]

Step 2: 10+13a=10+13a

Step 3: The expressions are equivalent because they both equal the same value.

(1 point)
Responses

10+12a+a=10+13a
d plus 10 plus a equals 10 plus a plus d

12a+10+a−a=10+a+12a−a
d plus 10 plus a equals 10 plus a plus d

12a+10=10+12a
d plus 10 plus a equals 10 plus a plus d

12a+10+a−10=10+a+12a−10

1 answer

To determine the missing step in proving the equivalence of \(12a + 10 + a = 10 + a + 12a\) using the Commutative Property, we can rearrange the terms in the expression.

The appropriate missing step would be restructuring the left-hand side of the equation.

Among the provided response options, the one that best represents this rearrangement is:

10 + 12a + a = 10 + 13a

This reflects the rearrangement of the expression correctly, and is consistent with the rules of the Commutative Property.